Analysis of Geogebra Applications and Manipulative Media in Proving the Level of Spatial Rotating Symmetry - Hidayati, Destia Wahyu; Sophie, Beguin; Sophie, Vandenhove; Baron, Grégory (Scientechno: Journal of Science and Technology, 2023)
Geometry is a sub-matter that exists in mathematics related to everyday life. The existence of an understanding related to geometry material has a positive impact on increasing spatial abilities from various points of view. The ability to see geometric shapes from various perspectives is related to rotation and rotational symmetry. Studying rotational symmetry and how rotation affects its appearance and geometric properties will help deepen your understanding of the overall geometric shape. The purpose of this study is to provide a description of the views to prove the level of rotational symmetry in geometric 3D shapes by considering the description of the advantages and disadvantages of using geogebra and manipulative application media which are adapted to their respective characteristics. This research is a qualitative research. Data collection techniques used are observation and interviews. The instruments used were observation sheets and interview sheets. The data analysis technique used is data triangulation. The research results obtained are proving the degree of rotational symmetry in geometric shapes which have 1) the advantages of using geogebra: it does not take long to prove, it is flexible regarding geometric dimensions and the determination of the symmetry axis, does not take up space/practical, is available in the form of applications and online websites 2 ) Weaknesses of using GeoGebra: having to use a PC/laptop, the ability of GeoGebra users to use it is the main variable, limitations on PC/laptop, or internet performance, 3) advantages of using manipulative media: easier and more real in observing the degree of rotational symmetry, display at each level the degree of rotational symmetry can be marked to facilitate calculations, 4) the weakness of using manipulative media: it takes time to make manipulative media, the media requires an appropriate size for practice, inflexibility regarding the size and placement of the axis of symmetry.